Parametric design strategy of a novel self-similar hierarchical honeycomb for multi-stage energy absorption demand. (1st March 2022) - Liang, Hongyu; Hao, Wenqian; Xue, Guilian; Liu, Baichuan; Pu, Yongfeng; Ma, Fangwu
Highlights: The representative unit cell (RVE) of CVH is divided into three sub-regions with independent thickness parameters according to the position of the hexagon. The influence of different thickness distributions on the performance of CVH is investigated to explore the conditions for the emergence of dual-platform features. Four key design parameters of the whole energy absorption process are extracted, which are derived theoretically based on the stable deformation modes. A detailed parametric design strategy of the CVH specimen is proposed based on the theoretical analysis, which can regulate the energy absorption curve to the required range. Abstract: The center-vertex honeycomb (CVH) structure based on the self-similar hierarchical evolution of the hexagonal honeycomb (HH) is introduced in this paper. The CVH structure has stable deformation modes, excellent energy absorption performance, and multi-platform features, and can be applied to multi-stage energy absorption devices with special requirements, such as energy-absorbing components of vehicles and trains. In this study, the multi-stage energy absorption characteristics of CVH under the in-plane quasi-static compression load are investigated numerically and theoretically, which is verified by the experimental test. The representative unit cell (RVE) of CVH is divided into three sub-regions with independent thickness parameters according to the position of the hexagon. The effects of different thickness distributions on the performance of CVH are investigated to explore the conditions for the emergence of dual-platform features. Then, the four key design parameters of the whole energy absorption process are extracted, which are derived theoretically based on the stable deformation modes. Further, a detailed parametric design strategy of the CVH specimen is proposed based on the specific engineering requirements. The design results proved that the proposed design strategy is reliable and accurate, which provides valuable suggestions and guidelines for the regulation of the energy absorption process of relevant structures for specific engineering needs. Graphical abstract: Image, graphical abstract